Hukum Pencurian Perspektif Tafsir Klasik dan Tafsir Kontemporer - Dikriyah Dikriyah; Nikhlah Ziyadaturrohmah; Siti Nur Azizah Azizah; Agus Ali Dzawafi (TADHKIRAH: Jurnal Terapan Hukum Islam dan Kajian Filsafat Syariah, 2025)
A comparison between classical and contemporary interpretations regarding the law of theft contained in Surah Al-Mā’idah verse 38, which stipulates the punishment of hand amputation for theft. This verse has long been the basis of Islamic jurisprudence, but its interpretation has evolved over time. The method used is qualitative with a literature study approach, which examines classical sources of interpretation such as Tafsīr al-Qurṭubī and contemporary interpretations such as al-Mishbāḥ. The research findings show that classical interpretations view this verse textually and normatively, with a focus on the application of hudud law as a form of justice and protection of property rights, as well as the imposition of strict conditions to avoid misuse. Meanwhile, contemporary interpretations view this verse contextually and humanistically, paying attention to social, economic, and humanitarian conditions. The punishment of hand amputation is understood not only as physical punishment, but also as a tool for moral education, crime prevention, and protection of community welfare. Although both share the same goal of upholding justice and safeguarding the welfare of the people, contemporary interpretations emphasize a more flexible application of law to align with the values ​​of social justice in the modern era. Thus, this study emphasizes the importance of contextualizing the understanding of Islamic law without neglecting the principles of sharia, which balance justice, humanity, and the welfare of the people.